A Purge and Trap-Gas Chromatographic Method for Determination of Chlorofluorocarbons in Seawater - Cai Ming-Gang; Huang Peng; Zhang Mi-Ming; Li Wen-Quan; 蔡明刚; 李文权 (ELSEVIER SCIENCE INC, 2013)
A purge and trap system was developed for the determination of chlorofluorocarbons (CFCs) in seawater. The optimum conditions were as follows: trap temperature of -60 degrees C, purge time of 8 min, purge flow rate of 20 mL/min, desorption time of 1.5 min, desorption temperature of about 130 degrees C. The method is simple and sensitive, the detection limit of CFC-11, CFC-12, CFC-113 and CCl4 were 0.004, 0.008, 0.001 and 0.006 pmol/L, and the recoveries of them were 99.92%+/- 1.77%, 98.77%+/- 1.50%, 98.95%+/- 3.92% and 97.13%+/- 1.78%, respectively. The R-2 values of all the calibration curves were greater than 0.99. This method was successfully used in the analysis of the samples collected in Prydz Bay in 27th Chinese Antarcitc Research Expedition.